Analysis of Virus-Derived siRNAs in Strawberry Plants Co-Infected with Multiple Viruses and Their Genotypes - Koloniuk, Igor; Matyášová, Alena; Brázdová, Sára; Veselá, Jana; Přibylová, Jaroslava; Várallyay, Eva; Fránová, Jana (Plants (Basel, Switzerland), 2023)
Plants can be infected with multiple viruses. High-throughput sequencing tools have enabled numerous discoveries of multi-strain infections, when more than one viral strain or divergent genomic variant infects a single plant. Here, we investigated small interfering RNAs (siRNAs) in a single strawberry plant co-infected with several strains of strawberry mottle virus (SMoV), strawberry crinkle virus (SCV) and strawberry virus 1 (StrV-1). A range of plants infected with subsets of the initial viral species and strains that were obtained by aphid-mediated transmission were also evaluated. Using high-throughput sequencing, we characterized the small RNA fractions associated with different genotypes of these three viruses and determined small RNA hotspot regions in viral genomes. A comparison of virus-specific siRNA (vsiRNA) abundance with relative viral concentrations did not reveal any consistent agreement. Strawberry mottle virus strains exhibiting considerable variations in concentrations were found to be associated with comparable quantities of vsiRNAs. Additionally, by estimating the specificity of siRNAs to different viral strains, we observed that a substantial pool of vsiRNAs could target all SMoV strains, while strain-specific vsiRNAs predominantly targeted rhabdoviruses, SCV and StrV-1. This highlights the intricate nature and potential interference of the antiviral response within a single infected plant when multiple viruses are present.
Keywords: vsiRNA; multistrain virus infection; strawberry virus; RNA silencing